Students Educational Problems Presented in the Universitys Educational Councils from 2002 to 2005 Shahrekord University of Medical Sciences - Seifollah BorjianBorujeni; Hedayatollah Shirzad; Soleiman kheiri; Zahra Haghshenas; Hossein Mirzavand; Ahmad Beigi; Bijan Nekouee (Kerman University of Medical Sciences, 2009)
Background & Objective : An educational council one of the most important parts of each university plays the main role in solving students educational problems This study was aimed to analyze the students educational problems in Shahrekord University of Medical Sciences according to the councils minutes from 2002 to 2005   Methods : In this study 333 cases of the students educational problems were extracted from the minutes of 66 educational councils meetings during a period of four years They were analyzed according to the students study field level turn (morning or evening courses) sex and the state of being native   Results : Among all request for omitting a course educational leave and registering a course were the most frequent problems Non native students educational problems were more than native ones (68% and 43% respectively) and males problems (98%) were more than females (38%) (p=00001) Educational problems among students of medicine (84%) radiology (76%) and field of fighting against diseases (59%) were more frequent than others The difference between the frequency of problems in the students attending morning classes (53%) and those attending evening classes (52%) was not significant   Conclusion : This study revealed that the students educational problems were different in various study fields There were significantly more problems in male and non native students (who are less supported by the families) compared to female and native ones Family financial and health problems lack of enough knowledge among students and tutors about educational rules stood amongst the most important factors leading to the students educational problems